2008
DOI: 10.1128/iai.00786-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Bile-Induced Exopolysaccharide Required for Salmonella Biofilm Formation on Gallstone Surfaces

Abstract: Salmonella enterica serovar Typhi can establish a chronic, asymptomatic infection of the human gallbladder, suggesting that this bacterium utilizes novel mechanisms to mediate enhanced colonization and persistence in a bile-rich environment. Gallstones are one of the most important risk factors for developing carriage, and we have previously demonstrated that salmonellae form biofilms on human gallstones in vitro. Thus, we hypothesize that bile-induced biofilms on gallstone surfaces promote gallbladder coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(160 citation statements)
references
References 42 publications
7
152
0
1
Order By: Relevance
“…Earlier studies have established the essential role of biofilm formation on gallstones removed from patients chronically infected with S. Typhi (Prouty et al, 2002). More recently, TBAs have revealed the bile-dependant enhancement of S. Typhi biofilms and specific binding to cholesterol-coated surfaces, such as in some cases of gallstones (Crawford et al, 2008). Furthermore, TBA's have also confirmed that the flagellin subunit fliCI is necessary for initial binding to cholesterol-coated surfaces.…”
Section: Persistencementioning
confidence: 59%
See 1 more Smart Citation
“…Earlier studies have established the essential role of biofilm formation on gallstones removed from patients chronically infected with S. Typhi (Prouty et al, 2002). More recently, TBAs have revealed the bile-dependant enhancement of S. Typhi biofilms and specific binding to cholesterol-coated surfaces, such as in some cases of gallstones (Crawford et al, 2008). Furthermore, TBA's have also confirmed that the flagellin subunit fliCI is necessary for initial binding to cholesterol-coated surfaces.…”
Section: Persistencementioning
confidence: 59%
“…In S. Typhi infected gallbladders, EPS is primarily composed of cellulose, colanic acid, Vi capsular antigen, curli fimbriae, O antigen capsule and biofilm associated proteins (Gibson et al, 2006;GonzalezEscobedo et al, 2011;Jonas et al, 2007;Ledeboer & Jones, 2005). Although the role of some elements in the EPS remain minor, other elements such as cellulose, colonic acid and O antigen capsule are crucial for S. Typhi persistence and biofilm development (Crawford et al, 2008;Prouty & Gunn, 2003;Prouty et al, 2002).…”
Section: Persistencementioning
confidence: 99%
“…Interestingly, bile has been shown to enhance S. Typhi biofilm formation (Gonzalez-Escobedo et al, 2011). Consistently, S. Typhi exhibits specific binding to cholesterol-coated surfaces, like gallstones (Crawford et al, 2008). FliC and OmpC are two proteins that were described to have a key role on initial adhesion to cholesterol-coated surfaces (Crawford et al, 2010).…”
Section: Biofilm Formationmentioning
confidence: 81%
“…The biofilm matrix is composed of EPS (extracellular polymeric substances) and water. Some components of biofilm EPS like cellulose, colonic acid and O antigen capsule are crucial for S. Typhi persistence and biofilm development (Crawford et al, 2008;Prouty and Gunn, 2003;Prouty et al, 2002). Some studies show that bile present in the gallbladder induces the production of O-antigen, which facilitates S. Typhi biofilm formation on human gallstones (Crawford et al, 2008;Hall-Stoodley and Stoodley, 2009).…”
Section: Biofilm Formationmentioning
confidence: 99%
“…However, other capsular polysaccharides can be present in the extracellular biofilm matrix of Salmonella strains (de Rezende et al, 2005;Gibson et al, 2006;White et al, 2003), and the exact composition depends upon the environmental conditions in which the biofilms are formed (Prouty & Gunn, 2003). Another component of the EPS matrix of Salmonella bile-induced biofilms, the O-antigen (O-ag) capsule, while it was found to be crucial for S. Typhimurium and S. Typhi biofilm development on gallstones, this was not necessary for adhesion and biofilm formation on glass and plastic (Crawford et al, 2008). The formation of this O-ag capsule was also found to be important for survival during desiccation stress .…”
Section: Molecular Components Of Salmonella Biofilms Formed On Abiotimentioning
confidence: 99%